Penggunaan Facebook Dalam Pembelajaran IPS di SMP Negeri 2 Sambas Kabupaten Sambas - Fitriani (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2023)
The purpose of this study is the application of distance learning using Facebook media at the SMP Negeri 2 Sambas level. The implementation of learning from home during the Covid-19 Pandemic through the WA group, raised new problems, where parents were bothered because of the many assignments given by the school. This research method used qualitative descriptive research. Primary data sources are social studies teachers, students at SMP Negeri 2 Sambas and school principals, while secondary sources are research journals and books that are relevant to supporting additional research data. Data collection tools used in the form of observation, interviews and documentation. The data analysis used is the Miles and Huberman Data Model consisting of; data reduction, data presentation, and drawing conclusions. The results of this study are that the implementation of distance learning in schools that is easy to use is the Facebook application/media. Group discussion activities at home can encourage students to be active in learning so that learning becomes creative and fun. Through the media Facebook, IT skills of teachers and students can be improved.